2007
DOI: 10.1104/pp.107.102582
|View full text |Cite
|
Sign up to set email alerts
|

Maize Brittle stalk2 Encodes a COBRA-Like Protein Expressed in Early Organ Development But Required for Tissue Flexibility at Maturity

Abstract: The maize (Zea mays) brittle stalk2 (bk2) is a recessive mutant, the aerial parts of which are easily broken. The bk2 phenotype is developmentally regulated and appears 4 weeks after planting, at about the fifth-leaf stage. Before this time, mutants are indistinguishable from wild-type siblings. Afterward, all organs of the bk2 mutants turn brittle, even the preexisting ones, and they remain brittle throughout the life of the plant. Leaf tension assays and bend tests of the internodes show that the brittle phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 53 publications
4
127
0
1
Order By: Relevance
“…The brittle culm (bc) mutants in rice show reduced tissue mechanical strength due to significant reductions in cellulose content, which is often accompanied by increased levels of lignin, as in the case of bc1, bc10, and bc12, each of which is affected in a different aspect of cellulose deposition (Li et al, 2003b;Zhou et al, 2009;Zhang et al, 2010). Similarly, the reduced cellulose content in mature stems of the spontaneous maize mutant brittle stalk2 (bk2), disrupted in a gene orthologous to the BC1 gene in rice, goes along with a marked enrichment in lignin deposition, resulting in brittleness of all aerial plant organs (Sindhu et al, 2007). In agreement with its corresponding mutant in rice, bk2 and wild-type plants were indistinguishable in all aspects of plant growth and development (Ching et al, 2006;Sindhu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brittle culm (bc) mutants in rice show reduced tissue mechanical strength due to significant reductions in cellulose content, which is often accompanied by increased levels of lignin, as in the case of bc1, bc10, and bc12, each of which is affected in a different aspect of cellulose deposition (Li et al, 2003b;Zhou et al, 2009;Zhang et al, 2010). Similarly, the reduced cellulose content in mature stems of the spontaneous maize mutant brittle stalk2 (bk2), disrupted in a gene orthologous to the BC1 gene in rice, goes along with a marked enrichment in lignin deposition, resulting in brittleness of all aerial plant organs (Sindhu et al, 2007). In agreement with its corresponding mutant in rice, bk2 and wild-type plants were indistinguishable in all aspects of plant growth and development (Ching et al, 2006;Sindhu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the reduced cellulose content in mature stems of the spontaneous maize mutant brittle stalk2 (bk2), disrupted in a gene orthologous to the BC1 gene in rice, goes along with a marked enrichment in lignin deposition, resulting in brittleness of all aerial plant organs (Sindhu et al, 2007). In agreement with its corresponding mutant in rice, bk2 and wild-type plants were indistinguishable in all aspects of plant growth and development (Ching et al, 2006;Sindhu et al, 2007). In brachypodium, the dwarf spaghetti1 (spa1) mutant presents a unique phenotype combining brittleness with increased elasticity of the internodes (Timpano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AtCOBL9 is required for tip-directed growth in root hair development in Arabidopsis (Parker et al 2000;Jones et al 2006). The rice brittle culm1 (bc1) mutant and the maize brittle stalk 2 (bk2) mutant were found to have mutations in the putative orthologs of AtCOBL4 that affected the mechanical strength of plant tissues and secondary cell wall biosynthesis Ching et al 2006;Sindhu et al 2007). Moreover, recent research has indicated that ZmBk2L1 is required for the root hair development in maize (Hochholdinger et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…11,13 The localized accumulation of cell wall-bound phenolics was visualized in cross-sections from equivalent root regions using UV-fluorescence microscopy 14 and by in situ staining for lignins. 15,16 Here, we used a surgical approach to determine whether the localized accumulation of wall cellulose or lignin occurred in stem tissues that provide stem strength.…”
mentioning
confidence: 99%